Mika Rottenberg - Bowls balls souls holes - Jørgensen, Lærke Rydal 1986-; Kold, Anders (Louisiana Museum of Modern Art, 2022)
Born in Argentina, raised in Israel and now living in New York, Mika Rottenberg (born 1976) explores connections between people in the global consumer society through film, installation, sculpture and drawing. In Rottenberg's work, people--most often women--and machines are engaged in incessant production. Rhythmic editing and sound design whirl us into labyrinthine processes in which goods are manufactured and conveyed in one big, surreal hamster wheel. Her scenarios are funhouse versions of our own world; like science labs investigating naturally occurring phenomena, the artist's installations can be seen as designs and models testing social concepts and abstract systems. Rottenberg herself calls her art "social surrealism."This catalog, designed by the internationally acclaimed Dutch designer Irma Boom, presents some of Rottenberg's most trenchant work, as well as an interview with the artist by Anders Kold, curator at the Louisiana Museum of Modern Art, and an introduction by William Pym. Exhibition: Louisiana Museum of Modern Art, Humlebaek, Denmark (25.09. - 18.12.2021)
Impressum: The catalogue is published on the occasion of the exhibition "Mika Rottenberg. Bowls balls souls holes", Louisiana Museum of Modern art, Humlebæk, Denmark, 25 September 2021 - 9 January 2022
Keywords: Rottenberg, Mika -- 1976-; Ausstellungskatalog -- Louisiana Museum of Modern Art -- 25.09.2021-09.01.2022 -- Humlebaek; Bildband